Enhance Cultural Tourism Expectations of Personalized Travelers in Ho Chi Minh City, Vietnam - Xuan Son, Doan (Global journal of Business and Integral Security, 2025)
Personalized travel allows you to put yourself first and take some time to relax and unwind, as well as venture out, explore, and do things you wouldn’t normally do. The study’s findings and lessons learned should help to effectively promote tourism and cultural events in Ho Chi Minh City, attracting more international travelers, especially those who love personalized travel. Furthermore, the thesis results can serve as a springboard for developing tourism in Ho Chi Minh City and Vietnam in general. Literature explores digital change, tourism experts, personalized travelers, cultural tourism, urban tourism, travel services, location management, and cultural tourism components, highlighting the impact of stakeholders and promoting Vietnamese culture. There is a shortage of standardized frameworks for assessing occupational skills standards in Vietnam’s tourism sector, and limited options for personalized travel experiences in the existing literature. This study use convenience sampling for quantitative research, targeting readily available individuals, while purposive sampling is utilized for qualitative research, integrating both quantitative and qualitative methodologies for thorough data collection. The tourist industry is experiencing substantial transformations as a result of technology innovations and globalization. Cultural tourism professionals require proficiency in communication, interpersonal skills, and specialized knowledge. Enhancing legal frameworks and policies is essential for advancing equity and optimizing the sharing economy.This research explores Vietnam’s personalized tourism market trends from 2020- 2027, focusing on Ho Chi Minh City and its potential advancement through technology applications. The study on cultural tourism in Ho Chi Minh City has limitations, including a small sample size, insufficient tourism expert participation, and insufficient data on diverse traveler perceptions, requiring further research.